Insights into the catalytic cycle and activity of methanol-to-olefin conversion over low-silica AlPO-34 zeolites with controllable Brønsted acid density. Issue 3 (19th January 2017) - Dai, Weili; Cao, Ge; Yang, Liu; Wu, Guangjun; Dyballa, Michael; Hunger, Michael; Guan, Naijia; Li, Landong
Abstract : The catalytic cycle and activity of methanol-to-olefin conversion over low-silica AlPO-34 zeolites can be effectively altered by changing the Brønsted acid density. Abstract : Low-silica AlPO-34 materials with similar crystal sizes but different Brønsted acid site densities were prepared and investigated as catalysts in methanol-to-olefin (MTO) conversion. The effect of Brønsted acid site density on catalyst activity and the dominant reaction mechanism during the MTO conversion was investigated via TGA, GC-MS, solid-state NMR spectroscopy, and in situ UV/vis spectroscopy together with the catalytic performance. For the catalysts with lower Brønsted acid site densities, the olefin-based cycle mechanism is the dominant mechanism during the MTO conversion. Long-chain alkenes, e.g., C5  –C6  alkenes, act as intermediates that are cracked to lower olefins, or are converted to dienes via hydride transfer reactions, and can also diffuse out of the cages of low-silica AlPO-34 catalysts as the products. With decreasing Brønsted acid site density or reaction temperature, the methylation route of the olefin-based cycle was found to be much more favored than the cracking route. Therefore, a higher selectivity to C5  –C6  alkenes (∼50%) is achieved. Simultaneously, dienes are the predominant deposits occluded in the used catalysts. For catalysts with slightly higher Brønsted acid site densities, the long-chain alkenes are rapidly transformed to aromatics and, subsequently, an aromatic-based cycle mechanism contributes to the MTO conversion. Interestingly, the catalyst with the most suitable Brønsted acid site density can well balance the above-mentioned two reaction cycles accompanied by a low deactivation rate, leading to a long catalyst lifetime of up to 15 h.